A Theory of Price Adjustment under Loss Aversion - Inske Pirschel; Steffen Ahrens; Dennis Snower (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper provides an alternative theory of price adjustment resting on consumer loss aversion in the price dimension. In line with prospect theory the perceived losses from price increases are weighted stronger in the consumer s utility function than the perceived gains resulting from price decreases of equal magnitude. Prices are evaluated relative to a certain reference price which is endogenous, sluggish and depends to the consumer s recent rational price expectations. Two key modeling implications arise: First, demand responses are more elastic for price increases than for price decreases and thus firms face a downward-sloping demand curve that is kinked at the consumer s reference price. Second, changes in the consumer s recent rational price expectations and hence in the consumer s reference price can alter demand through what we call the reference-price-updating effect. We incorporate this into an otherwise standard dynamic neoclassical model of monopolistic competition and analyze price and quantity reactions to various demand shocks. We find that although firms may change their prices flexibly, depending on the size of the shock the prices adjust more or less pronounced than in the standard monopoly model and that prices can even be rigid. Additionally, we find that the price adjustment is asymmetric with respect to shock size and sign and the current state of the business cycle, i.e. pricing is state-dependent.
Keywords: D03; D21; E31; 330